LEADING CHANGE THROUGH THE PEKA (ANTI-VIOLENCE AND ANTI-BULLYING PREVENTION, COUNTERMEASURES, AND CAMPAIGNS) PROGRAM: BUILDING CONCERN AND TOLERANCE IN THE MIDST OF DIVERSITY - Vika, Laila Vika Safitri; Jatiningsih, Oksiana; Warsono, Warsono (Kajian Moral dan Kewarganegaraan, 2025)
This study aims to evaluate the implementation of the PEKA Program (Prevention, Countermeasures, and Anti-Violence and Anti-Bullying Campaign) at SMK Negeri 2 Surabaya as a systematic effort to reduce and prevent bullying in the school environment. Bullying is a serious problem that has a negative impact on students' physical, psychological, and social health, so a comprehensive and collaboration-based approach between all elements of the school is needed. The research method used was descriptive qualitative with a mixed methods approach, involving data collection through quantitative surveys, in-depth interviews, and participatory observations with Grade 10 students, teachers, and parents. Data analysis was conducted using descriptive statistics to measure changes in bullying cases and thematic analysis to explore stakeholders' perceptions and experiences related to program implementation. The results showed that the PEKA Program succeeded in reducing various forms of bullying, such as physical bullying, verbal bullying, and social exclusion with a total decrease in cases of 57.1%. The application of the gotong royong principle integrated in the program and the use of digital flipbook media as an interactive educational tool proved effective in increasing students' awareness of the importance of cooperation, empathy, and respect for differences. In addition, the program was able to create a more inclusive, safe and conducive school environment for learning. However, the research also identified challenges related to the sustainability of the program, particularly the need for ongoing training for teachers as well as increased parental involvement in supporting bullying prevention. This study concludes that the PEKA Program makes a significant contribution to students' character building based on Pancasila values as well as a model that can be replicated in other schools to create a learning environment free from bullying. Keywords: bullying, mutual cooperation, character education, PEKA program.